Community Empowerment: Through The CAHAYA YBM PLN Village Program From The Educational Perspective In North Lombok Regency - Hadi, Zahrul; Musawar, Musawar; Azkar, Muh. (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This research aims to investigate the community empowerment program through the CAHAYA YBM PLN Village Program from an educational perspective in North Lombok Regency. The research method used is qualitative with a case study approach. Data collection techniques include in-depth interviews with various stakeholders, participatory observation, and documentary study. Data analysis employs thematic analysis to identify major thematic patterns related to the impacts of the empowerment program. The findings indicate that the CAHAYA YBM PLN Village Program has significantly positive impacts on the local community. The program successfully enhances the quality of life by improving access to electricity, education, and skills training. In conclusion, this community empowerment program contributes significantly to enhancing local capacity in managing resources sustainably. The implications of this research underscore the need for continuous support for community empowerment programs like CAHAYA YBM PLN to ensure the sustained benefits for the community.